1996
DOI: 10.1111/j.1460-2695.1996.tb01023.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient Fatigue Crack Growth Behaviour Following Single Overloads at High Stress Ratios

Abstract: Fatigue crack growth tests with constant amplitude loading and single overload have been performed on a long mode I crack in 2017-T3 aluminium alloy at various stress ratios from 0 to 0.7. Two crack tip parameters of uop and u, were evaluated using a finite element analysis for a growing crack under these loading conditions. The former is the crack opening stress and the latter is the applied stress level at which the stress at the crack tip becomes tensile. It was found that transient crack growth behaviour f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
8
24
0
Order By: Relevance
“…Table 3, the described trends were observed for all the DK BL analysed in this work at both R ratios of 0.05 and 0.25. Therefore, the magnitude and extent of crack retardation increase with the level of the OLR, accordingly to many other studies [1,2,12,15,18].…”
Section: Transient Crack Growth Behavioursupporting
confidence: 70%
See 2 more Smart Citations
“…Table 3, the described trends were observed for all the DK BL analysed in this work at both R ratios of 0.05 and 0.25. Therefore, the magnitude and extent of crack retardation increase with the level of the OLR, accordingly to many other studies [1,2,12,15,18].…”
Section: Transient Crack Growth Behavioursupporting
confidence: 70%
“…Finite element analyses have shown that this phenomenon can occur depending on the loading variables [14,25]. Tsukuda et al [18] have also corroborated the existence of discontinuous closure at high stress ratios due to single tensile overloads by finite element analysis. This investigation indicates that the stress at the crack tip becomes tensile before the crack fully opens at the overload location.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several mechanisms have been proposed to explain crack growth retardation; including models based on residual stresses, crack closure, crack tip blunting, strain hardening, crack branching and reversed yielding. The effect of residual plastic deformation leads to compressive stresses in the wake of the crack and raises the crack opening load on subsequent crack growth (crack closure), becoming the most important phenomena in explaining the variation of the characteristic features of postoverload transients [19][20][21][22][23]. Donald and Paris [23] observed for 6061-T6 and 2024-T3 aluminium alloys, that closure measurements produced a good data correlation between different stress ratio crack growths obtained with K-increasing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Overloads can lead to significant interaction effects on crack propagation, as have been reported in many [11][12][13][14][15][16][17][18][19][20][21][22]. Several mechanisms have been proposed to explain crack growth retardation; including models based on residual stresses, crack closure, crack tip blunting, strain hardening, crack branching and reversed yielding.…”
Section: Introductionmentioning
confidence: 99%